The Effect of Digital Chat and Phone Marketing in Increasing Patient Repeat Orders Through Closing Rate in Men's Health Services in Indonesia - Elnardy, Mohammad Caesario; Zaharuddin, Zaharuddin; Kusuma, Sitta (International Journal of Business, Law, and Education, 2026)
This study aims to analyze the influence of chat-based and telephone-based digital marketing on patient closing rates and repeat orders, and to examine the mediating role of closing rates in this relationship. The research employed a quantitative, survey-based approach with non-clinical healthcare workers serving as medical advisors in men's health clinics in Indonesia. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to identify both direct and indirect relationships among variables. The findings reveal that digital marketing via chat and phone significantly affects patient conversion rates and repeat orders. Furthermore, closing rate was found to mediate the relationship between chat and telephone communication and repeat order behavior. These results indicate that the effectiveness of digital marketing strategies in healthcare services is not solely determined by the utilization of digital technology but also by the quality of communication demonstrated by healthcare personnel. The study highlights the importance of structured and strategic digital communication in strengthening patient engagement and loyalty. The findings provide practical implications for healthcare service providers, particularly clinic management, in developing more effective digital marketing strategies that emphasize communication quality, patient trust, and relationship continuity.